The Impact of Adult Child Emigration on the Mental Health of Older Parents - Irene Mosca; Alan Barrett (Institute for the Study of Labor (IZA), 2014)
A growing literature within economics has sought to examine the impacts of emigration on sending countries. Some of the studies have looked within families and have investigated how emigration affects those family members who are left behind. In this paper, we explore whether older parents of adult children who emigrate experience declines in mental health compared to parents whose children do not migrate. We use data from the first two waves of The Irish Longitudinal Study on Ageing. This is a nationally representative sample of 8,500 people aged 50 and above living in Ireland collected in 2009-11 (Wave 1) and 2012-13 (Wave 2). To deal with the endogeneity of migration, we apply fixed effects estimation models and control for a broad range of life-events occurring between the two waves. These include the emigration of a child but also events such as bereavement, onset of disease, retirement and unemployment. We find that depressive symptoms and feelings of loneliness increase among the parents of migrant children but that the effect is only present for mothers. Given the relationship between mental health and other health outcomes, the potential impacts for the older populations of migrant-sending regions and countries are significant.
Keywords: I15; J61; 330; emigration; depression; mental health